53.7k views
4 votes
x³+ax²+bx+6 has (x-2) as factor and leaves remainder 3 when divided by (x-3), find values of a and b​

2 Answers

4 votes

Step-by-step explanation:

this is your answer....

x³+ax²+bx+6 has (x-2) as factor and leaves remainder 3 when divided by (x-3), find-example-1
x³+ax²+bx+6 has (x-2) as factor and leaves remainder 3 when divided by (x-3), find-example-2
User Mohamed Rahouma
by
4.2k points
4 votes

P(x) = x^3 + ax^2 + bx + 6

________________________________

Reminder :

x - a = 0 ==》 x = a

P(a) = Reamaining of the diving P(x) by

( x - a )

________________________________

x - 2 = 0 ==》x = 2 ==》P(2) = 0

(2)^3 + a(2)^2 + b(2) + 6 = 0

8 + 4a + 2b + 6 = 0

4a + 2b + 14 = 0

4a + 2b + 14 - 14 = 0 - 14

4a + 2b = - 14

( 4a + 2b ) ÷ 2 = ( -14 ) ÷ 2

2a + b = - 7 ( ♡ )

_________________________________

x - 3 = 0 ==》 x = 3 ==》P(3) = 3

(3)^3 + a(3)^2 + b(3) + 6 = 3

27 + 9a + 3b + 6 = 3

9a + 3b + 33 = 3

9a + 3b + 33 - 33 = 3 - 33

9a + 3b = - 30

( 9a + 3b ) ÷ 3 = ( - 30 ) ÷ 3

3a + b = - 10 ( ☆ )

________________________________

( ♡ ) , ( ☆ ) in pair system of equation

( ☆ ) : 3a + b = - 10 3a + b = - 10

====》

( ♡ ) : 2a + b = - 7 × (-1) - 2a - b = + 7

___________ +

a = - 3

So :

2( - 3 ) + b = - 7

- 6 + b = - 7

- 6 + 6 + b = - 7 + 6

b = - 1

¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥

Thus : a = - 3 & b = - 1

User ShemTov
by
4.6k points